Prosiding Simposium Persatuan Biologi Gunaan Malaysia Ke-11, 2010 “Keseimbangan Biologi Ke Arah Kelestarian Hayat” : Feasibility of Fungus Bioaugmentation in Sawdust Composting - Rohanie, B. (2010)
In this study, theability of selected ligninolytic fungus in accelerating composting rate was evaluated. From two-stage screening of lignin degrading ability, Cerrena unicolor was selected as inoculumfor this sawdust composting trial. Comparative effects on physiochemical changes of inoculated sawdust and non-inoculated sawdust were evaluated within 3 months. The study showed that application of C. unicolor as inoculum gave a significant effect on composting rate. It was observed that the compost was ready to be used within 3 months. Maturity of compost was determined by germination test, nursery trial and physiochemical analysis.